Review article of Vicharchika (Eczema) (International Journal of Food and Nutritional Sciences, 2021)
The present paper is based on Ayurvedic disease “Vicharchika kushtha.” Here we can compare it modern skin disease “Eczema”. Eczema is defined as a specific type of allergic cutaneous manifestation of antigen antibody reaction characterized by superficial inflammatory oedema of epidermis associated with vesicle formation and itching. These features of Eczema correlates with the features of Vicarcika. Therefore some scholars have correlated these two with each other. There are many references for Ayurvedic management of Vicharchika kushtha that we have to apply in modern time. Finally main intention for presenting this paper is to share basic details of Vicharchika Kushtha for proper Treatment.